Pathogenicity Test and Molecular Characterization of Colletotrichum spp. Fungi Causing Apple Fruit Rot Disease in Malang Regency - Maknunin, Lu'lu'il; Abadi, Abdul Latief; Syib'li, Muhammad Akhid (Direktorat Riset dan Pengabdian Masyarakat, Universitas Brawijaya, 2023)
Apple (Malus sylvestris Mill) is a key commodity in Malang Regency, Indonesia, because of its role in promoting the agrotourism sector. But fruit rot caused by Colletotrichum spp. poses significant threats to production and its existence. This study aims to identify the causal agents of fruit rot in apple orchards in Pujon District, Malang, using morphological and molecular approaches. Four isolates suspected to be Colletotrichum spp. were obtained from symptomatic apple fruits and characterized through macroscopic, microscopic, and molecular methods, including ITS sequencing. Pathogenicity tests revealed that all isolates induced symptoms on healthy apples, with Colletotrichum siamense confirmed as the primary pathogen via BLAST analysis. These findings emphasize the need for accurate morphological and molecular identification to develop effective management strategies. Further research is recommended to examine the diversity of Colletotrichum species in Malang Regency to inform broader disease control strategies.